Analisis Usaha Tani dan Pola Tanam Komoditi Buah Naga (Hylocereus undatus) dan Lada (Piper Ningrum L) di Kecamatan Loa Janan Kabupaten Kutai Kartanegara - Zainudin Zainudin; Akhmad Sopian (Agrifarm : Jurnal Ilmu Pertanian, 2016)
This research was conducted in order to obtain information system cropping patterns and farming in the District Loa Janan to increase cropping intensity in order to support the development of site-specific dryland farming insightful agribusiness. This research is also expected to result in the value of R / C ratio greater than 1 so that it is economically feasible to be implemented at the farm level. This study aims to conduct inventory of characteristics of land such as: climate, relief, topography, soil type, and land use, mengidentivikasi pattern of farmers planting dragon fruit and pepper in the village Batuah, knowing the cost and farm income commodity dragon fruit and pepper, as well as determine the feasibility of farming based on the analysis of R / C ratio. This research uses descriptive method with interviews with respondents sampled, namely farmers dragon fruit and pepper farmers in the village of Loa Janan Regency. The results showed by climatic conditions, topography and land more feasible to develop commodity pepper from the dragon fruit, both in monoculture and mixed farms. Overall analysis of farm commodities and pepper dragon fruit has a value of R / C ratio> 1, which means that the commodity still worth to be cultivated. Based on the analysis of capital productivity (? / C ratio) commodity pepper is more feasible to be developed because it is larger than bank interest, while the dragon fruit is smaller than bank interest. Based on the factors of production of farm commodities dragon fruit significant influence, such as land, seed and fertilizer.